Pembuatan Media Pembelajaran Agama Islam Pada Masa Pandemi Virus Covid 19 Berbasis Podcash Sosial Media Musik Spotify di Politeknik Negeri Media Kreatif PSDKU Medan - Gunawan Gunawan; Murtopo Murtopo; Akmal Walad Ahkas (Intiqad: Jurnal Agama dan Pendidikan Islam, 2021)
The spread of the Covid 19 Virus has halted learning activities at all levels of learning and hampered social distancing. This has made every educator and policymaker in the education world turn their heads to develop learning media. Internet-based media is a mandatory choice that must be done, so media applicators are competing to create learning media. Spotify Social Media Podcast is an internet-based application that is quite popular in the United States and various countries in Europe, even profitable for business, but not yet popular enough in Indonesia. The potential audience is quite large, because, in addition to being able to be heard on the street by commuters, about 30% of the population are auditory learners. For this reason, a literature study was carried out which aims to explore opportunities for audio podcasts to develop learning media at the Politeknik Negeri Media Kreatif PSDKU Medan, as well as content analysis of several podcast content providers sites that are quite successful in Indonesia. The results of the study indicate that the audio podcast optimization strategy includes the development of podcast materials; the approach and distribution of content according to the needs, desires, and ways of students consuming audio content; and the suitability of the content with the character and orientation of the media. In addition, this effort must also be accompanied by an intensive campaign through various means. State the research objectives and targets to be achieved and the methods that will be used in achieving these goals.